Integrated Phytomineral Synergy: The Essential Role of Oligoelements (Mg, Fe, K) in the Antioxidant and Anti-infective Activities of Myrothamnus moschatus - Hanitriniaina, Natafita Carène; Razafimahatratra, Jean Hugues; Soavina, Silvère Augustin; Manjovelo, Christian Sambany; Ngbolua, Koto-Te-Nyiwa Jean Paul; Fatiany, Pierre Ruphin; Rahelivololoniaina, Baholy Robijaona (Budapest International Research in Exact Sciences (BirEx) Journal, 2025)
Myrothamnus moschatus, commonly known as the "resurrection plant," stands as an emblematic species of Southern Madagascar, traditionally valued as a tonic and an anti-infective remedy. While prior investigations primarily focused on the volatile fraction (essential oils), the present study pioneers the exploration of the non-volatile mineral fraction in relation to the plant's significant biological activities. Elemental analysis of the aerial part's powder revealed a high content of magnesium (1.17%), iron (0.60%), and potassium (0.50%), with no detectable traces of heavy metals (Pb, Cd, Hg, As). Simultaneously, extracts exhibited high antioxidant activity (IC50 =12.99μg/mL), a moderate yet significant antiplasmodial inhibition (Plasmodium berghei, 34.44% at 500mg/kg ; p=0.01395), and marked antibacterial activity against Staphylococcus aureus (16.25mm). The confluence of a protective mineral profile and measured bioactivities confirms that the plant's efficacy stems not only from its secondary metabolites but also from functional inorganic cofactors, thereby establishing it as a true regenerating tradiphytoremedy. These findings reposition M. moschatus as an integrative pharmacognostic resource, paving the way for standardized phyto-mineral formulations for anti-infective and prophylactic purposes.